On the timing option in a futures contract - Francesca Biagini; Tomas Björk (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
The timing option embedded in a futures contract allows the short position to decide when to deliver the underlying asset during the last month of the contract period. In this paper we derive, within a very general incomplete market framework, an explicit model independent formula for the futures price process in the presence of a timing option. We also provide a characterization of the optimal delivery strategy, and we analyze some concrete examples. Futures contract ; timing option ; optimal stopping
Keywords: G12; G13; 330; Termingeschäft; Optionspreistheorie; Unvollkommener Markt; Suchtheorie; Theorie